2015
DOI: 10.1111/scs.12236
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in German home‐care arrangements

Abstract: An ageing population correlates with rising needs for long-term care (LTC). Support programmes should consider the specific needs of the various subgroups of care dependents and family caregivers. The objective of this study was to analyse the gender-specific disparities in home-care arrangements in Germany, and for this purpose, survey and insurance claims data were used. A survey of 2545 insured care recipients with high-level care needs was conducted in 2012 with the Barmer GEK, a major German statutory hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
7
0
7
Order By: Relevance
“…Studies that did focus on care arrangements including informal care did not report on possible gender differences in sufficient detail (e.g., Bakker et al, 2013; von Kutzleben et al, 2015); thus, data allowing a comparison of our findings with earlier dementia studies are missing, and the role of gender differences in the utilization of informal support networks remains unknown. However, a study on gender disparities in German home-care arrangements found that in a sample of high-need insured respondents who were 60 years and older, most men received care from their wives, whereas widowed women depended on their social networks and children to remain in their homes instead of transferring to residential LTC (Dorin, Krupa, Metzing, & Buscher, 2015). These authors concluded that policy makers and researchers must emphasize family and social networks to provide better home-care arrangements for women without a partner who are in need of high-level care; second, they stated that the wives of men with high-level care needs require more support to provide stable home-care situations (Dorin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that did focus on care arrangements including informal care did not report on possible gender differences in sufficient detail (e.g., Bakker et al, 2013; von Kutzleben et al, 2015); thus, data allowing a comparison of our findings with earlier dementia studies are missing, and the role of gender differences in the utilization of informal support networks remains unknown. However, a study on gender disparities in German home-care arrangements found that in a sample of high-need insured respondents who were 60 years and older, most men received care from their wives, whereas widowed women depended on their social networks and children to remain in their homes instead of transferring to residential LTC (Dorin, Krupa, Metzing, & Buscher, 2015). These authors concluded that policy makers and researchers must emphasize family and social networks to provide better home-care arrangements for women without a partner who are in need of high-level care; second, they stated that the wives of men with high-level care needs require more support to provide stable home-care situations (Dorin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on gender disparities in German home-care arrangements found that in a sample of high-need insured respondents who were 60 years and older, most men received care from their wives, whereas widowed women depended on their social networks and children to remain in their homes instead of transferring to residential LTC (Dorin, Krupa, Metzing, & Buscher, 2015). These authors concluded that policy makers and researchers must emphasize family and social networks to provide better home-care arrangements for women without a partner who are in need of high-level care; second, they stated that the wives of men with high-level care needs require more support to provide stable home-care situations (Dorin et al, 2015). Our data suggest that the same might be true for care arrangements in dementia.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of authors have focused on analyzing cash‐for‐care schemes from the perspective of informal caregivers (Arksey and Glendinning ; Schmid et al ; Ungerson , ), little is known about the reasoning underlying the ways in which different types of care are accessed and combined in a cash‐for‐care scheme from the perspective of older care recipients themselves (Klie and Blinkert ; Lundsgaard ; Theobald and Kern ). Also, with some exceptions, gender differences in the experience of growing old have been hardly explored in previous works (Calasanti ), and being female (or male) is used as an individual attribute when analyzing determinants of LTC use rather than as a category to analyze inequalities (Einiö et al ; Schmidt ; Dorin et al ). Addressing this gap, we focus on the oldest old (80+), an age group where LTC needs are particularly widespread (BMASK ), and these are going to increase in the future with the rise in chronic diseases and multimorbidity (European Commission ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that older women use more formal care than older men (Einiö et al ., 2012; Dorin et al ., 2016), while older men use more informal care (McCann et al ., 2012), and especially spousal care, than women (Dorin et al ., 2016; Schmidt, 2017). The differences in morbidity and mortality between older women and men are considered important drivers of these gender differences in long-term care (LTC) use.…”
Section: Introductionmentioning
confidence: 99%